First data on latent tuberculosis infection in Syrian refugees with diabetes in Lebanon. (December 2020) - Ismail, M.B.; Nour, D.; Raad, G.; Osman, M.; Rafei, R.; Mallat, H.; Dabboussi, F.; Hamze, M.
Abstract: Objective: The association between diabetes mellitus and tuberculosis is a health-threatening double trouble. Vulnerable populations such as refugees and conflict-displaced populations may be at higher risk of both diseases. Here, we examined the prevalence of latent tuberculosis infection (LTBI) and its associated risk factors in a population of Syrian refugees with diabetes in North Lebanon. Study design: This is a cross-sectional study. Methods: A total of 87 Syrian refugees with diabetes were enrolled. Demographic and clinical data were collected using a structured questionnaire, and a blood sample was obtained from each patient. LTBI was examined using the last generation QuantiFERON-TB Gold Plus assay. Results: The mean age of the study population was 54.1 ± 10.5 years, and the majority were women (79.3%). LTBI was found in 1 in 5 (17/87; 19.5%) enrolled patients, with the majority being originated from Aleppo (47.05%). Infection was significantly associated only with age ( P = 0.009), and its risk was 4-fold higher in patients aged ≥60 years (odds ratio: 4.1, confidence interval: 1.4–12.5, P = 0.018). Conclusion: This study highlights the need to implement effective tuberculosis control strategies among refugees with diabetes, with particular attention to those at older age. Highlights: Prevalence of latent tuberculosis among Syrian refugees with diabetes never investigated. One of 5 Syrian refugees with diabetes in Lebanon has a latent tuberculosis infection. Older age is significantly associated with tuberculosis infection in this population. TB control measures should be implemented among refugees with diabetes, esp. elders. Diabetes-TB requires intl. efforts & resource mobilization in humanitarian settings.